Developing an expert system method for assessment of destructive information-psychological influence - Bilal Zahran; Jamil AL-Azzeh; Andrii Gizun; Vladyslav Griga; Bogdana Bystrova (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
Nowadays solving practical problems in various sectors using intelligent solutions, based on expert systems are becoming more and more widespread. In this paper an expert system method is proposed for assessment and prediction of destructive influences. All disadvantages of existing assessment systems are taken into account during the development and analysis phases. The most important estimated parameters are determined. This method is based on quantitative methods of expert evaluation, which gives the advantage: there is no need to collect large amounts of statistical data and clear formalization of the current situation.